2018
DOI: 10.1021/acsami.7b13541
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of V–Fe–Cr–Ti Solid State Hydrogen Storage Materials in Impure Hydrogen Gas

Abstract: Two approaches of engineering surface structures of V-Ti-based solid solution hydrogen storage alloys are presented, which enable improved tolerance toward gaseous oxygen (O) impurities in hydrogen (H) gas. Surface modification is achieved through engineering lanthanum (La)- or nickel (Ni)-rich surface layers with enhanced cyclic stability in an H/O mixture. The formation of a Ni-rich surface layer does not improve the cycling stability in H/O mixtures. Mischmetal (Mm, a mixture of La and Ce) agglomerates are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Hydrogen splitting occurs at the interface between the oxidized rare-earth metal and the TiFe phase in the alloy. This is due to the fact that Ti, Fe, Mn, and Co have a higher hydrogen separation potential than that of La and Ce [13,17,18]. This can explain why the "poisoned alloy" can still absorb hydrogen after 15 cycles, while the source alloy hardly absorbs any hydrogen.…”
Section: Cyclic Stability Mechanism Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen splitting occurs at the interface between the oxidized rare-earth metal and the TiFe phase in the alloy. This is due to the fact that Ti, Fe, Mn, and Co have a higher hydrogen separation potential than that of La and Ce [13,17,18]. This can explain why the "poisoned alloy" can still absorb hydrogen after 15 cycles, while the source alloy hardly absorbs any hydrogen.…”
Section: Cyclic Stability Mechanism Analysismentioning
confidence: 99%
“…They found that La plays an important role in the cyclic stability of the alloys. Ulmer et al [13] studied the effect of adding rare-earth metals on the cyclic stability of V-Fe-Cr-Ti alloy in impure hydrogen gas. They found that adding rare-earth metals can improve the cycling stability in hydrogen containing oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that most of the alloy is well-protected by the surface in a spent NiMH battery after the battery has reached its end of life [2]. In another recent paper, the presence of rare-earth metals was suggested as a reason for the beneficial corrosion stability [7]. This provided the inspiration for trying a new method for regeneration of MH electrode materials by simply cleaning and washing the powder surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Seeking a compact, efficient, and safe manner to store hydrogen is a key challenge for using it as an energy carrier in a more sustainable future society. One feasible option is solid-state storage in hydrides. Numerous hydrides have been studied and evaluated for their hydrogen storage properties, and the scope of study has expanded from conventional metal hydrides and sorbent materials to complex hydrides, including alanates, borohydrides, amides/imides, ammonia borane, and amidoboranes. In particular, sodium alanate, NaAlH 4 , was the first complex hydride to be considered for mobile hydrogen storage applications because of suitable thermodynamics and relatively high hydrogen density . Theoretically, 7.5 wt % H 2 or 94 g H 2 /L is stored in NaAlH 4 by the following three-step reaction, but only the first two steps (5.6 wt % H 2 ) are practically available because of the high decomposition temperature of NaH (>400 °C) …”
Section: Introductionmentioning
confidence: 99%
“…For pure NaAlH 4 , the release and uptake of hydrogen have to surmount a high kinetic barrier with reported reaction activation energy of approximately 120 kJ/mol, which makes the materials reversible only under extreme conditions (270 °C and 175 bar of H 2 ). Hope that NaAlH 4 could be utilized as a practical hydrogen storage medium was generated in 1997 by Bogdanovićand Schwickardi, who successfully achieved reversible hydrogen storage with it under much milder conditions by doping in a few mole percent of β-TiCl 3 or Ti(OBu) 4 . 17 After that, tremendous effort has been devoted to developing catalyst-doped NaAlH 4 , and a large number of catalysts, ranging from transition-metal compounds, rare-earth metal compounds to carbon-based materials, have been screened and studied.…”
Section: Introductionmentioning
confidence: 99%